Hyperosmolar therapy for acute brain injury: study protocol for an umbrella review of meta-analyses and an evidence mapping. Issue 2 (6th February 2020) - Badenes, Rafael; Hutton, Brian; Citerio, Giuseppe; Robba, Chiara; Aguilar, Gerardo; Alonso-Arroyo, Adolfo; Taccone, Fabio Silvio; Tornero, Carlos; Catalá-López, Ferrán
Abstract : Introduction: Acute brain injury is a challenging public health problem worldwide. Elevated intracranial pressure is a common complication after acute brain injury. Hyperosmolar therapy is one of the main therapeutic strategies for the management of intracranial hypertension. This study protocol outlines an umbrella review of meta-analyses which will investigate the benefits and harms of hyperosmolar therapy routinely used for the management of acute brain injury in the intensive care. Methods and analysis: We will search PubMed/MEDLINE, EMBASE and the Cochrane Database of Systematic Reviews. We will include meta-analyses of primary research studies (eg, randomised controlled trials, observational studies or both) that evaluate one or more hyperosmolar solutions (including hypertonic saline and/or mannitol) for the treatment of adult patients with acute brain injury of any severity. Two researchers will independently screen all citations, full-text articles and abstract data. Potential conflicts will be resolved through discussion with a third researcher. Primary outcomes will be mortality and neurological outcomes at discharge. Secondary outcomes will include control of intracranial pressure, cerebral perfusion pressure, length of stay (in hospital an intensive care unit) and any adverse event. Quality of the included meta-analyses will be assessed using the AMSTAR-2 tool. An overall summary of methods and results will be performed using tabular and graphical approaches and will be supplemented by narrative description. We will analyse whether published meta-analyses present an outline of available evidence (eg, cited, described and discussed any previous meta-analysis). Where objectives from two or more meta-analyses overlap, we will assess the causes of any noted discrepancies between meta-analyses. Ethics and dissemination: No ethical approval will be required. Findings from this study will be published in a peer-reviewed journal. All data will be deposited in a cross-disciplinary public repository. PROSPERO registration number: CRD42019148152.